The association between dietary consumption habits and psoriasis: a two-sample Mendelian randomization study - Minghui, Lu; Changyong, Gao; Runtian, Zhang; Jianhong, Li; Lingling, Yuan; Xi, Chen (Frontiers in Nutrition, 2024)
Background: Psoriasis is a chronic inflammatory skin disease characterized primarily by erythema and scales, having a wide-ranging impact globally. Previous studies have suggested that dietary consumption habits may influence psoriasis. The objective of this study was to determine the causal relationship between dietary consumption habits and psoriasis using the Mendelian Randomization (MR) approach. Methods: SNP data for 29 dietary consumption habits and psoriasis were obtained from the GWAS catalog database and the FinnGen database, respectively. The Mendelian Randomization analysis was performed using R software, with the 29 dietary consumption habits as the exposure factors and psoriasis as the outcome. Three MR analysis methods-Inverse Variance Weighted (IVW), Weighted Median Estimator (WME), and MR-Egger regression-were employed to study the causal relationship between dietary consumption habits and psoriasis. Results: The IVW analysis indicated an OR (95%CI) of 0.065 (0.008-0.555), P = 0.012, demonstrating a negative correlation between the consumption of dried fruit and psoriasis. Conclusion: Among the 29 dietary consumption habits analyzed, the intake of dried fruits is a protective factor against psoriasis. Therefore, it is clinically advisable to appropriately increase the intake of dried fruits among patients with psoriasis, serving as a nutritional therapy method in conjunction with pharmacological treatment.